2015
DOI: 10.1038/nature15703
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of fairness in seven societies

Abstract: A sense of fairness plays a critical role in supporting human cooperation. Adult norms of fair resource sharing vary widely across societies, suggesting that culture shapes the acquisition of fairness behaviour during childhood. Here we examine how fairness behaviour develops in children from seven diverse societies, testing children from 4 to 15 years of age (n = 866 pairs) in a standardized resource decision task. We measured two key aspects of fairness decisions: disadvantageous inequity aversion (peer rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
355
5
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(427 citation statements)
references
References 30 publications
34
355
5
5
Order By: Relevance
“…Importantly, a robustly observed feature of such pure cooperation is that, despite playing a key role in promoting the collective good, the extent to which people cooperate with strangers varies markedly across cultures (Blake et al, 2015; Cappelen, Moene, Sørensen, & Tungodden, 2013; Gächter, Herrmann, & Thöni, 2010; Henrich et al, 2005; Henrich et al, 2010; Sapienza, Zingales, & Guiso, 2006; Yamagishi, Hashimoto, & Schug, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a robustly observed feature of such pure cooperation is that, despite playing a key role in promoting the collective good, the extent to which people cooperate with strangers varies markedly across cultures (Blake et al, 2015; Cappelen, Moene, Sørensen, & Tungodden, 2013; Gächter, Herrmann, & Thöni, 2010; Henrich et al, 2005; Henrich et al, 2010; Sapienza, Zingales, & Guiso, 2006; Yamagishi, Hashimoto, & Schug, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…In a comparison across a diverse set of communities, House et al [92] found that, while children in all communities enter society with a similar prosocial tendency, they will, as they grow older, adjust their behaviour to the cross-culturally variable prosocial norms of their community. Reflecting this, in an intriguing study, Blake et al [93] probed reactions to disadvantageous inequity aversion (DI-the avoidance of receiving less than a peer) and advantageous inequity aversion (AI-the avoidance of receiving more than a peer) in children aged 4-9 years across seven distinct cultures (Canada, India, Mexico, Peru, Senegal, Uganda and the US). DI was present in all societies, with cultural variance in its age of emergence, appearing earliest in the US and Canada, latest in Mexico.…”
Section: Prosocialitymentioning
confidence: 99%
“…The great majority of psychological research has been conducted in populations that are unrepresentative of human culture globally and historicallythose from Western, educated, industrialized, rich, and democratic (WEIRD) backgrounds (38,69). A growing literature within developmental psychology and the anthropology of childhood aims to correct the bias in studying WEIRD populations within the discipline (18,37,38,(70)(71)(72)(73)(74)(75)(76)(77)(78).…”
mentioning
confidence: 99%